PEMAAFAN (FORGIVENESS) DAN PSYCHOLOGICAL WELLBEING PADA NARAPIDANA WANITA - Raudatussalamah dan Reni Susanti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2014)
Appreciation and good religious experience has a considerable influence on the physical andmental health and can improve psychological wellbeing. Psychological wellbeing is an important requirement.These needs can be obtained by instilling religious and moral values one of which is to forgive. This study tries toexplore the subjective quality of life associated with psychological well-being of women prisoners in prisons II BPekanbaru in relation to forgiveness.Research data collection using a scale of forgiveness and psychological wellbeing with forgiveness scalevalidity of test results ranged 0.271 to 0.763. While the scale of psychological wellbeing validity of the test resultsobtained 0.261 to 0, 674. Based on the obtained reliability test forgiveness scale reliability coefficient of 0.829 and0.817 scale of psychological wellbeing. Normal distribution of data and linear correlation coefficient r obtained at0.387 with a significance level of 0.000 (p <0.001). Contributions forgiveness of psychological wellbeing by15%. Thus the proposed hypothesis there is a relationship between forgiveness (Forgiveness) with psychologicalwellbeing in women inmates is accepted. Forgiveness related to welfare by changing the mind, emotions andbehaviors negative to a positive response